Language as a Tool for Social Inclusion: Experiences of Multilingual Learners in Migrant Contexts in Uzbekistan - Khodiyakhon Sodikova (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
This study explores how language shapes the social and academic experiences of multilingual learners from migrant families in Uzbekistan. Drawing on classroom observations and teacher reflections, it examines how limited language proficiency can affect students’ participation, sense of belonging, and academic progress. The findings show that migrant students often struggle to fully engage in class and build peer relationships, which can slow their learning compared to native students. However, supportive teacher practices—such as flexible grouping and emotionally responsive teaching—can help reduce anxiety and foster inclusion. The study highlights the importance of language-sensitive and inclusive pedagogy in increasingly diverse educational settings.